ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL STRUCTURE DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Effendi, Bahtiar (Universitas Multimedia Nusantara, 2024)
Abstract - Most businesses are founded to achieve maximum profit. Almost all companies compete for maximum profits. Profit is the most important measurement tool for a company's success. A company's profitability is the outcome of a series of financial strategies and operational choices implemented by the organization. This study seeks to ascertain whether corporate social responsibility (CSR), sales growth, and firm size influence the firm's capital structure, with the firm's profitability as an intervening variable. This research focuses on manufacturing companies listed on the Indonesian Stock Exchange (IDX) during the period 2019-2022. This research is quantitative in nature. It includes manufacturing firms and employs purposive sampling as the sampling method. The data analysis involves path analysis, hypothesis testing, and coefficient of determination (R2) analysis using SPSS version 26.00 software. The findings indicate that corporate social responsibility (CSR) and sales growth do not influence capital structure, while company size significantly affects capital structure. Profitability, serving as an intervening variable, influences corporate social responsibility, sales growth, and company size, all of which significantly impact the company's capital structure. Keywords: Corporate Social Responsibility; Sales Growth; Company Size; Capital Structure; Profitability